The Implementation of Total Sanitation Programme Based of Community - Stop Defecating Carelessly in the Lembur Timur and Luba Village Subdistrict Lembur of Alor District on 2015 - Yosef Yusran (JURNAL KESEHATAN LINGKUNGAN, 2017)
Nationally data show that no province in Indonesia to reach the targets of the Millennium Development Goals in 2015, that is 100% access to the toilets. Open defecation behavior is the main cause in occurrence of disease based environment. This research was conducted to describe the implementation process of the first pillar a program called Community Based Total Sanitation, "Stop Open Defecation” in the Lembur Timur and Luba Village, District Alor subdis– Lembur on 2015. This research was evaluative draft summative approach system descriptive analyzed. The interview was carried out in public health centre and village on 14 people that implementing Community Based Total Sanitation. The subjects of Reviews These studies were taken in purposive sampling. In-depth interviews, examination of documents and observations conducted to get a more information about the variables Examined. Variable in this Research was process of the program. Research results showed variable training facilitator, plan of action, natural leader as well as monitoring and evaluation were eligible with Permenkes No. 3 on 2014 about Community Based Total Sanitation, whereas the variabel of trigger and advocacy were not eligible. There were no document trigger and recommendations written advocacy activities related to the government of the village. Community empowerment efforts haven't been running because not maximal formed Village Community Based Total Sanitation Committee. Need to increase the knowledge of sanitarian with conduct a study and comparative study to other public health centre with the recording system and reporting as well as the establishment of Village Community Based Total Sanitation Committee.